Food inflation examination through the dynamic nexus between olive oil and substitutes - Nikolaos A. Kyriazis (Economies, 2023)
This study provides insights into food inflation by investigating the dynamic interconnectedness of the prices of olive oil, soybean oil, sunflower oil, and palm oil. Using data from January 1990 to October 2023, averaged dynamic and extended joint connectedness analyses are conducted by employing the innovative Time-Varying Parameter Vector Autoregressive (TVP-VAR) methodology. The findings reveal that olive oil presents a low connection with substitute oils and generates net spillover effects, especially at the onset of COVID-19 but also at later stages and during the Russia-Ukraine war. Palm oil transmits effects on the system of oils before the Global Financial Crisis (GFC) but renders a net receiver afterward, while sunflower oil follows the opposite way. Systemic connectedness is the highest during the GFC and remains elevated during QE-tapering. It slightly increases during COVID-19 outbursts and illustrates higher spikes when the Russia-Ukraine conflict begins. These linkages are even stronger among only the substitute oils
Keywords: 330; olive oil; food inflation; COVID-19; Russia–Ukraine war; TVP-VAR; dynamic connectedness